(3fXe GdeYdheGJ GdeMGSHjIs - (3eMeO jhSa(B, (3GdMafGhjs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2000)
(3JcfhdhLjG GdeYdheGJ GdeMhSHI(B-(3JQcjHI fXGe GdeYdheGJ GdeMGSHjI(B-(3eYGdLI GdHjGfGJ GdeGdjI GdeONdI heNQLGJ GdfXGe(B-(3OhQGJ eYGdLI GdeYGedGJ(B-(3JWhjQ fXGe GdeYdheGJ GdeMGSHjI(B-(3GdHQeLjGJ GdeMGSHjI GdeYGdLI(B-(3GdQbGHI hGdJObjb hGdCef GdeSJfO ddMGSHs
(3HHdjhZQGajG(B: (3U(B.321s
Keywords: (3GdeMGSHIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s